Analisis Laporan Keuangan Serta Tata Cara Pengelolaannya Pada Yayasan Galang Bersama Kami Sebagai Lembaga Filantropi Islam - Zia’ul Bati Pradiksa; Vitayanti Fattah; Muhammad Yunus Kasim; Risnawati Risnawati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The main objective of this research is to analyze the financial reports managed by the Galang Bersama Kami Foundation (YGBK) as a non-profit institution that focuses on raising funds from donors in the form of Zakat, Infaq, Alms and Waqf (ZISWAF) funds. Which is about where the Foundation's funds come from, and how the Foundation provides the allocation flow. For this purpose, the author used quantitative descriptive research methods, with direct observation techniques to related parties, followed by interviews and special documentation during data collection. After conducting interviews, the author found that the entire set of YGBK funds came from 3 things, namely from ZISWAF funds, CSR funds from agencies/companies, and potential businesses from our Joint Business Institutions. The funds raised will be channeled to the Foundation's program and operational funds, the distribution percentage of which is based on BAZNAS regulation Number 1 article 8 of 2016 specifically for ZISWAF funds. The percentage of CSR distribution depends on the Foundation's agreement with the CSR provider company. Meanwhile, the proceeds from our Joint Business will be distributed in full to the Foundation's operational costs. The percentage of the Foundation's financial reports shows a decrease in income from 2022 to 2023 of 49%. All of this is done to provide transparent and open financial management for the people in order to maintain their sense of trust in the Galang Bersama Kami Foundation.